Career Management and Employees’ Performance in the Ministry of Education and Vocational Training in Zanzibar - Bacar, Mina; Suleiman, Shabaan Mwinchum; Haroonah, Nsubuga (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aimed at examining the relationship between career management and employees’ performance in Ministry of Education and Vocational Training (MoEVT) in Zanzibar. Survey research design was employed in this study due to its nature. Data was collected from 95 respondents using questionnaires survey. In order to reach a credible result, an inferential statistical technique was used such as Pearson’s Correlation coefficient was used as a data analysis technique to measure the relationship between career management and employee performance in the MoEVT. The findings of the study revealed that, career management correlates moderately with the employee performance by 0.416 (42%). This means that, the increase of career management in the organisation does also lead to increase in employee performance. The study concludes career management can influence the employees’ performance by 42 percent only. The study recommends for more improvement in human resources policies in order to achieve better performance as well as higher productivity.